2022
DOI: 10.20517/cdr.2021.85
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ICIs on patients with oncogene-driven non-small cell lung cancer: a retrospective study

Abstract: Aim: The objective of our study was to assess the efficacy of immune checkpoint inhibitors (ICIs) on patients with non-small-cell lung cancer (NSCLC) harboring oncogenic alterations. Methods: We retrospectively enrolled patients with advanced non-squamous NSCLC who were treated with anti-PD-1-based monotherapy or combined immunotherapy. Major characteristics including PD-L1 expression, treatment, and survival were analyzed. Results: In total, 309 non-squamous NSCLC patients with a median age of 61 years (ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A meta-analysis reported that patients with EGFR mutations did not benefit from ICI monotherapy as a second-line therapy compared to docetaxel [9]. Consistent with prior findings [22][23][24], the EGFR subtype in the present study did not benefit from ICI treatment in terms of mPFS across all subgroups, even for the high-TPS group (≥50%).…”
Section: Discussionsupporting
confidence: 86%
“…A meta-analysis reported that patients with EGFR mutations did not benefit from ICI monotherapy as a second-line therapy compared to docetaxel [9]. Consistent with prior findings [22][23][24], the EGFR subtype in the present study did not benefit from ICI treatment in terms of mPFS across all subgroups, even for the high-TPS group (≥50%).…”
Section: Discussionsupporting
confidence: 86%
“…Currently, immunotherapy or immunochemotherapy, depending on the level of PD-L1 expression, remains the standard of care for the first-line treatment of NSCLC. This also applies to patients with the p.G12C mutation in the KRAS gene, in whom the efficacy of immune checkpoint inhibitors is comparable to that in other patients [40][41][42][43][44][45]. Clinical trials are underway to evaluate the value of sotorasib in combination with other cancer drugs in first-line treatment (NCT05920356, NCT04933695) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, recent research [44] showed that several gene alterations (such as EGFR-mutant, ROS1 rearrangement, HER2 mutation) may affect the efficacy of immunotherapy in NSCLC.…”
Section: Discussionmentioning
confidence: 99%